Distance Learning Course for Healthcare Professionals: Continuing Education in Tuberculosis - Cabral, Vagner Kunz (Telemed J E Health, 2017)
Background: Continuing education of healthcare workers (HCWs) is an essential strategy for the control of tuberculosis (TB) transmission, enabling HCWs in early detection and appropriate treatment of TB cases. Methods: We developed a distance learning (DL) course on TB for nurses. We conducted a quasi-experimental before and after study to evaluate the DL community at the participant's learning level. In addition, to evaluate the DL community at the level of participant satisfaction, a cross-sectional study was carried out after the course. Nurses involved in active inpatient or outpatient care of patients were recruited to participate in the study. Results: Sixty-six participants started and completed the course and they were included in the analysis. The overall mean pretest and post-test scores were 10.3 ± 2.2 and 11.4 ± 2.7, respectively. Participants increased their knowledge to a statistically significant degree (p < 0.0001). At baseline, the frequency of correct answers was very low in some questions: number of people infected by Mycobacterium tuberculosis in the world (10.6%); number of TB cases in Brazil (36.4%); contagiousness of latent TB infection (LTBI) (28.8%); and definition of active case finding (45.5%). Course feedback was mostly positive, with majority of users saying they were satisfied or totally satisfied. Conclusions: A brief DL course on TB was associated with some improvement in knowledge among nurses. The baseline knowledge was low regarding TB epidemiologic data, concepts on LTBI, and active case finding. This finding emphasizes the need to further improve the competencies and knowledge of nurses.